Датчики на поверхностных акустических волнах для дистанционного контроля температуры - Kataev, V. F.; Bagdasariyan, A. S.; Karapetyan, G. Ya.; Dneprovski, V. G. (PE "Politekhperiodika", Book and Journal Publishers, 2008)
The proposed sensor enables the creation of systems for wireless remote temperature monitoring in hard-to-reach places, as well as various biological objects.